An Analysis of the Effectiveness of Different Types of Lids in Managing Urban Storm Water - Bhargav P. Majmundar; Girish Parmar (International Journal of Engineering and Management Research, 2023)
City increase is one such phenomenon that drives deep changes in land use patterns. From a hydrological perspective, urbanization will increase the impervious surfaces, which end result lower of infiltration and boom of runoff. This consequences is a boom in runoff extent and glide that could reason flooding, watercourse and habitat destruction. In recent state of affairs several Indian cities have witnessed remarkable incidences of flooding due to numerous reasons. Defective urban planning and failure of drainage gadget are taken into consideration as principal motives in the back of flooding and surface inundation in urban regions in growing countries. Most important question stand up that how runoff from new tendencies must be controlled? For that the use of SWMM (Storm Water Management Model) for specific Low Impact Development (LID) as gear for lowering runoff as well as discharge in the storm drainage.